2003
DOI: 10.1242/jeb.00610
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for nest-odour recognition in two species of diving petrel

Abstract: SUMMARY In nearly every procellariiform species, the sense of smell appears to be highly adapted for foraging at sea, but the sense of smell among the diving petrels is enigmatic. These birds forage at considerable depth and are not attracted to odour cues at sea. However, several procellariiform species have recently been shown to relocate their nesting burrows by scent, suggesting that these birds use an olfactory signature to identify the home burrow. We wanted to know whether diving petrels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 19 publications
5
51
0
Order By: Relevance
“…Many Procellariiform seabirds are able to home to their burrow using olfactory cues. Using Y-maze experiments it has been shown that many Procellariiforms significantly prefer an arm of a Y-maze associated with their own burrow scent over that of a conspecific (for example Bonadonna et al, 2003b). The burrow odours are probably composed of feces and feathers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Procellariiform seabirds are able to home to their burrow using olfactory cues. Using Y-maze experiments it has been shown that many Procellariiforms significantly prefer an arm of a Y-maze associated with their own burrow scent over that of a conspecific (for example Bonadonna et al, 2003b). The burrow odours are probably composed of feces and feathers.…”
Section: Resultsmentioning
confidence: 99%
“…This should not be surprising, since the penguins' closest relatives, the Procellariiforms (Hackett et al, 2008), appear to use olfaction in a social context (e.g. Bonadonna and SanzAguilar, 2012) and in nest recognition (Bonadonna et al, 2003b), in addition to foraging (reviewed in Nevitt, 2008). Nevitt (1999) first introduced the concept of an olfactory landscape, suggesting that Procellariiform seabirds are able to locate productive areas of the ocean by orienting towards scented areas of high primary productivity.…”
Section: Introductionmentioning
confidence: 99%
“…All of these studies reported poorer or null homing performances of anosmic birds compared with controls, emphasizing the crucial role of a functional sense of smell for homing at night. In addition, a number of behavioural studies carried out with Y-maze choice tests demonstrated the capacity of different species of procellariiforms for distinguishing between their own and a conspecific's burrow only by odour, as if the burrows had an individual olfactory signature (Bonadonna et al, 2003a;Bonadonna et al, 2003b;Bonadonna et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…At the intra-specific level, they are known to emit chemical compounds, which are important in several aspects of avian life histories (Caro & Balthazart 2010). For example, birds can recognize their nest using chemical cues (Mínguez 1997, O'Dwyer et al 2008, Bonadonna & Bretagnolle 2002, Bonadonna et al 2003a,b, 2004, de León et al 2003, Caspers & Krause 2011 and they are able to discriminate the scent of their partners from the scent of other conspecifics (Bonadonna & Nevitt 2004, Jouventin et al 2007. Therefore, chemical cues may play a role in social behaviour (Hagelin 2007).…”
mentioning
confidence: 99%